Future changes in extreme precipitation indices over Korea. (17th January 2018) - Kim, Gayoung; Cha, Dong‐Hyun; Park, Changyong; Lee, Gil; Jin, Chun‐Sil; Lee, Dong‐Kyou; Suh, Myoung‐Seok; Ahn, Joong‐Bae; Min, Seung‐Ki; Hong, Song‐You; Kang, Hyun‐Suk
ABSTRACT: In this study, the regional climate of the Korean Peninsula is dynamically downscaled using a high‐resolution regional climate model forced by two representative concentration pathway scenarios of Hadley Centre Global Environmental Model version 2‐Atmosphere and Ocean (HadGEM2‐AO) using multiple regional climate models. Changes in extreme precipitation indices are investigated. Through the evaluation of the present climate, a multi‐model ensemble reasonably reproduces the long‐term climatology of extreme precipitation indices over South Korea despite some systematic errors. Both mean and extreme precipitation intensities for 80 years in the future (2021–2100) increase compared to those of the present. However, the increasing rates of indices related to precipitation intensities are different according to sub‐period, season, and emission scenarios. Mean and extreme precipitation intensities of the future climate increase during the summer when most extreme precipitation events occur over the Korean Peninsula. Also, abnormal extreme precipitation can increase during future summers due to increasing variances of indices related to extreme precipitation intensity. Increasing extreme summer precipitation over South Korea is proportional to the increases in convective precipitation compared to non‐convective precipitation. This indicates that future changes in summer precipitation, with regard to intensity and frequency, over South Korea, among representative concentration pathway scenarios, are more related to a change in convective instability rather than synoptic condition. Abstract : This figure shows multi‐model ensemble (MME) rate of change in six indices between future (2021–2100) and present (1981–2005) scenarios (%). Dashed lines denote the areas where all RCMs reproduce the same sign of indices. Overall extreme precipitation intensity as well as mean precipitation intensity increases in the future. Also, model results from the five RCMs are consistent in the regions with a high rate of change for the indices, implying that the changes in indices are highly reliable in that region.